The audiovisual distribution of branded content through YouTube: The case of “Aprendemos Juntos” - Capapé Poves, Elena; Romero Calmache, María (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
YouTube is one of the most popular platforms to produce and distribute audiovisual content. Thus, brands take advantage of its potential to develop branded content projects. This paper addresses the case of “Aprendemos Juntos” by BBVA. The research aims to describe the distribution model and analyse the content to understand its key elements. The methodology is based on que quantitative analysis of the channel’s production (2019-2023) and a qualitative content analysis of the most relevant videos.